2022
DOI: 10.1016/j.healun.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to SARS-CoV-2 adenovirus vector vaccination (ChAdOx1 nCoV-19 [AZD1222]) in heart transplant recipients aged 18 to 70 years of age

Abstract: Background Recent studies have suggested a blunted immune response to messenger RNA vaccines in solid organ transplant (SOT) recipients. Given the paucity of data on adenovirus vector vaccines use in immunosuppressed SOT recipients, we sought to describe the safety and immunogenicity of the ChAdOx1 nCoV-19 vaccine in a heart transplant population. Methods Heart transplant recipients aged 18 – 70 years scheduled to receive 2 doses of the ChAdOx1 nCoV-19 vaccine were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…ChAdOx1 nCoV-19 appeared to have ble immunogenicity in patients with varying degrees of immunocompromised statu tably, ChAdOx1 nCoV-19 has shown promising immunogenicity in ESRD patient HD compared with those undergoing kidney transplantation [33]. Similarly, ChA nCoV-19 did not work well in heart transplant recipients [34]. On the other hand, pa with HIV had favorable immune responses after two doses of ChAdOx1 nCoV-1…”
Section: Discussionmentioning
confidence: 99%
“…ChAdOx1 nCoV-19 appeared to have ble immunogenicity in patients with varying degrees of immunocompromised statu tably, ChAdOx1 nCoV-19 has shown promising immunogenicity in ESRD patient HD compared with those undergoing kidney transplantation [33]. Similarly, ChA nCoV-19 did not work well in heart transplant recipients [34]. On the other hand, pa with HIV had favorable immune responses after two doses of ChAdOx1 nCoV-1…”
Section: Discussionmentioning
confidence: 99%
“…in the Israeli cohort in association with postdose 3 results. 5 , 6 In the current study, a mycophenolate‐based regimen was numerically more likely in those with a nondetectable antibody response compared to detectable (80% vs. 62%) but only trended toward significance ( p = .08), likely reflecting the modestly smaller numbers completing this study. Furthermore, shorter time interval since transplant and triple versus dual immunosuppressant regimens were significantly more common in those with a nondetectable response; similar signals were seen in both the postkidney transplant population in the randomized clinical trial noted above and a recent meta‐analysis on SOT recipients.…”
Section: Discussionmentioning
confidence: 56%
“…Each patient had a known antibody status after each of the initial two vaccines from phase one of our study. 5 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,11 The overall seroconversion rate ranged from 20.7% to 71.9% and most studies described reduced seroconversion (and lower serum concentration of antibodies) in patients receiving MMF compared to patients receiving MMF-free immunosuppression regimes. In some studies, a dose-dependent impairment of the humoral response was observed, 6,8,9,16 particularly when daily dose of MMF was higher than 1000 mg per day. 8 In all, 11 studies allowed quantitative synthesis comprising 2694 solid organ transplant recipients, 67.9% of them receiving MMF-containing immunosuppression regimes.…”
Section: Mycophenolate and Sars-cov-2 Vaccination: Mixing Oil And Watermentioning
confidence: 99%